2020
DOI: 10.1038/s41598-020-68163-3
|View full text |Cite
|
Sign up to set email alerts
|

Soil labile organic carbon fractions and soil enzyme activities after 10 years of continuous fertilization and wheat residue incorporation

Abstract: Labile organic carbon (LOC) fractions and related enzyme activities in soils are considered to be early and sensitive indicators of soil quality changes. We investigated the influences of fertilization and residue incorporation on LOC fractions, enzyme activities, and the carbon pool management index (CPMI) in a 10-year field experiment. The experiment was composed of three treatments: (1) no fertilization (control), (2) chemical fertilizer application alone (F), and (3) chemical fertilizer application combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 51 publications
4
66
0
1
Order By: Relevance
“…This suggested that the N fertilization effects on central tendency and spatial distribution of oxidases depended on the nature of the oxidase. However, the consistently negative correlations between oxidases (e.g., PER , PHO ) and soil organic carbon and total nitrogen and an absence of correlation with microbial biomass and some glycosidases were also identified (Table 3), which corroborated the synergistic behavior of the two oxidases involved in soil organic carbon cycling across treatments and crop species (Hassan et al, 2013; Sinsabaugh, 2010a; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This suggested that the N fertilization effects on central tendency and spatial distribution of oxidases depended on the nature of the oxidase. However, the consistently negative correlations between oxidases (e.g., PER , PHO ) and soil organic carbon and total nitrogen and an absence of correlation with microbial biomass and some glycosidases were also identified (Table 3), which corroborated the synergistic behavior of the two oxidases involved in soil organic carbon cycling across treatments and crop species (Hassan et al, 2013; Sinsabaugh, 2010a; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…N fertilization can induce significant impacts on the expression, excretion, and function of soil extracellular oxidases (Matocha et al, 2004; Zhang et al, 2020). N fertilizer markedly enhanced potential activities of PER in a 10‐year field experiment in a wheat–corn rotation system (Zhang et al, 2020). However, N fertilization suppressed soil PHO activity in no‐tillage cropland systems (Matocha et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Soil organic matter and SOC are the indicators most widely studied to determine the effects of crop residue removal (Zhang et al., 2020) and are highly influenced by crop residue management (Benjamin et al., 2008; Huggins et al., 1998; Kendall et al., 2015; Zhang et al., 2020). Barber (1979) studied the effect of returning 0, 100 and 200% corn stover, and fallow for 6 years followed by 5 years of 100% corn stover return in continuous corn for 11 years on a silt loam soil in Indiana.…”
Section: Crop Residue Management Effects On Soil Quality Parametersmentioning
confidence: 99%
“…Although residue harvest may provide several benefits, for example, the reduction of pest and disease pressure (Wilhelm et al., 2004), concerns have arisen about potential negative impacts because they act both as sinks and sources of soil carbon that provide important ecosystem services (Su et al., 2020). Crop residues contribute to agricultural productivity by reducing soil erosion and enhancing soil physical properties (Raffa et al., 2014; Wilhelm et al., 2007) through their positive effects on soil organic carbon (SOC), nutrient availability, bulk density, water holding capacity and water infiltration (Barber, 1979; Blanco‐Canqui & Lal, 2009; Franzluebbers, 2002; Kenney, 2011; Zhang et al., 2020). However, there are still many tradeoffs and insecurities about the dependence on agronomic (e.g., residual management, tillage intensity and fertilization rate) and abiotic (e.g., soil characteristics, climate conditions) parameters.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, straw incorporation into the soil is essential to SOC sequestration, and thus to improving soil fertility and mitigating climate change ( Wu et al., 2019). In recent years, numerous studies have recommended straw incorporation as a key practice to manage SOC stock and its fractions in agricultural ecosystems ( Xu et al., 2011; Han et al., 2018; Wu et al., 2019; Luo et al., 2020; Zhang et al., 2020). Zhu et al.…”
Section: Introductionmentioning
confidence: 99%